Sistem Informasi Kepegawaian pada Kantor Dinas Transmigrasi dan Tenaga Kerja Kabupaten Ende Berbasis Web - Egidius Eja; Kristianus Jago Tute; L.B Finansius Mando (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
At the Office of Transmigration and Manpower in Ende Regency, there are still some problems in terms of processing personnel data because it has not fully utilized the staffing system because it only uses ordinary office applications, namely using Microsoft Excel or Word, which has weaknesses in the data input process because it requires sufficient time. long. The purpose of this study was to design an application for the Civil Service Information System at the Office of the Transmigration and Manpower Office of Ende Regency WEB-Based. The research method used is a type of qualitative research. The collection technique in this study used the method of observation, interviews and literature study. The system development method uses the waterfall and the test uses black box testing. Conclusion of the Personnel Information System at the Office of Transmigration and Manpower in Ende Regency. This Web-Based database collects data needed in staffing such as employee data, payroll data, mutation data, rank/class data, SK data, position data, employment status data, and this website was created and designed using the PHP programming language and MySQL database.